Muslim Education in Post- independent India: Past, Present and Future - Intakhab Alam Khan (Journal of Education and Learning (EduLearn), 2016)
The real journey of education in general and higher education in particular in India started after 1947. Education is its journey can’t stand alone but institutional roles need to be included to assess the contribution as a whole. The institutions of higher learning are considered the most important agency of social change, social transformation, and entire development of the country. Muslim education has always been a serious issue despite availability of so many academic institutions in general and minority institutions in particular. The poor condition of the Muslims’ education can’t be attributed to the government only, but the society, home, economy, motivation, employment and similar factors. The present article is a modest attempt towards exploring and analyzing the miserable state of Muslim education and associated factors.